2020
DOI: 10.15252/emmm.202012993
|View full text |Cite
|
Sign up to set email alerts
|

MOTS‐c promotes phosphorodiamidate morpholino oligomer uptake and efficacy in dystrophic mice

Abstract: Antisense oligonucleotide (AO)‐mediated exon‐skipping therapies show promise in Duchenne muscular dystrophy (DMD), a devastating muscular disease caused by frame‐disrupting mutations in the DMD gene. However, insufficient systemic delivery remains a hurdle to clinical deployment. Here, we demonstrate that MOTS‐c, a mitochondria‐derived bioactive peptide, with an intrinsic muscle‐targeting property, augmented glycolytic flux and energy production capacity of dystrophic muscles in vitro and in vivo, resulting in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 47 publications
0
10
0
Order By: Relevance
“…A recent study also indicated that administration of MOTS-c elicited therapeutic levels without any detectable toxicity. 18 The evidence indicated that MOTS-c might be a more effective and safer peptide than drugs or microRNAs in the clinical treatment of CVD.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study also indicated that administration of MOTS-c elicited therapeutic levels without any detectable toxicity. 18 The evidence indicated that MOTS-c might be a more effective and safer peptide than drugs or microRNAs in the clinical treatment of CVD.…”
Section: Discussionmentioning
confidence: 99%
“…Previous research has shown that MOTS-c was naturally muscle-targeting, which could speed up skeletal muscle metabolism while generating energy [ 31 ]. MOTS-c increases the level of glycolysis and ATP in dystrophic muscle cells, enhancing the absorption and activity of phosphorodiamidate morpholino oligomer [ 31 ].…”
Section: Mots-c Inhibits Pathological Metabolic Processesmentioning
confidence: 99%
“…Previous research has shown that MOTS-c was naturally muscle-targeting, which could speed up skeletal muscle metabolism while generating energy [ 31 ]. MOTS-c increases the level of glycolysis and ATP in dystrophic muscle cells, enhancing the absorption and activity of phosphorodiamidate morpholino oligomer [ 31 ]. Additionally, it was found that by giving a long-term combined administration of MOTS-c and phosphorodiamidate morpholino oligomer to Duchenne muscular dystrophy (DMD)-affected mice, their muscular functions significantly improved [ 31 ].…”
Section: Mots-c Inhibits Pathological Metabolic Processesmentioning
confidence: 99%
See 1 more Smart Citation
“…Different approaches have been under intense scrutiny for enhancing the delivery of AOs to muscle including cell‐penetrating peptides (Moulton & Moulton, 2010), tissue‐targeting peptides (Gao et al , 2014), chimeric (Yin et al , 2010), and energy‐replenishing peptides (Ran et al , 2021), though the safety of these peptides remains to be determined. Synthetic or biological nanoparticles such as polymers or exosomes have also been utilized to enhance AO delivery to dystrophic muscles (Falzarano et al , 2014; Gao et al , 2018).…”
Section: Introductionmentioning
confidence: 99%